A Liquid-Phase reaction strategy to construct aqueous Sodium-Ion batteries anode with enhanced redox reversibility and cycling stability. (15th June 2023) - Lu, Meiling; Li, Ting; Yang, Xiaoqiang; Liu, Yue; Xiang, Xingde
Graphical abstract: Highlights: A novel liquid-phase reaction strategy is proposed to construct NaTi2 (PO4 )3 /C material. Construction mechanism and electrochemical properties of the material are understood. The material exhibits enhanced redox reversibility and cycling stability. Abstract: NASICON-type NaTi2 (PO4 )3 compound is strongly considered to be a promising anode material for aqueous sodium-ion batteries, but suffering from low redox reversibility and poor cycling stability due to severe side reactions in aqueous electrolytes. Herein, a novel liquid-phase reaction strategy is reported for in-situ constructing carbon-coated NaTi2 (PO4 )3 nanocrystals (C-NTP) with enhanced redox reversibility and cycling stability. The construction mechanism, structural properties and electrochemical performance of the C-NTP material are carefully investigated. It is suggested that the material possesses a mesoporous carbon-coating structure and delivers outstanding performance with a high reversible capacity of 114.5 mAh·g −1 at 100 mA·g −1 and an impressive capacity retention of 82.1% after 1000 cycles at 1000 mA·g −1 . The enhanced redox reversibility and cycling stability are attributed to the unique carbon-coating structure that improves the reaction kinetics and structural stability of the material owing to the high electronic conductivity and corrosion-resistant ability.